Characterization of Tropospheric Gradients for the Ground‐Based Augmentation System Through the Use of Numerical Weather Models. Issue 4 (3rd October 2017) - Guilbert, Alizé; Milner, Carl; Macabiau, Christophe
Abstract: In the scope of the Single European Sky Air Traffic Management Research (SESAR) Work Package 15.3.7, a number of research threads are being undertaken to improve the performance of multi‐constellation multi‐frequency ground‐based augmentation system to support CAT II/III precision approaches. Several challenges and key issues must be solved including those related to atmospheric modeling. However, there are a number of arguments for revisiting this topic and specifically addressing the tropospheric threat. First, recent observations, reported at the last International Civil Aviation Organization Navigation System Panel meeting, showed unexpected atmospheric behavior. The source could be related to a non‐modeled behavior of the troposphere. Second, in the advent of dual‐frequency ground‐based augmentation system, the main contributor to the atmospheric error will come from the tropospheric delay. That is why this paper explains a methodology to reassess the tropospheric threat within two main steps: an analysis of European meteorological data and an analysis of a new bounding methodology for dealing with the troposphere threat and its impact on vertical protection levels. Copyright © 2017 Institute of Navigation